PENGARUH KUALITAS LAYANAN ELEKTRONIK, NILAI YANG DIRASAKAN DAN KEPERCAYAAN YANG DIRASAKAN TERHADAP LOYALITAS ELEKTRONIK PADA BELANJA TERHUBUNG - Wiry Utami (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2018)
The purpose of this study is to examine the influence of electronic service quality, perceived value, perceived trust and e-loyalty in online shooping. Data for this study were collected by offline and online survey and administered to 237respondents. The hypothesis testing was conducted using  simple regression analysis and multiple regression analysis. The study found that there is positive and significant relationship between electronic service quality and perceived value, electronicservicequality and perceived trust, perceived value and e-loyalty and perceived trust and e-loyalty. Consequently, based on findings, electronic service quality, perceived value, perceived trust areconsidered to be antecendent of e-loyalty.